Hydrogen Sulfide Prevents Sleep Deprivation-Induced Hippocampal Damage by Upregulation of Sirt1 in the Hippocampus - Zuo, Jin-Xi; Li, Min; Jiang, Li; Lan, Fang; Tang, Yi-Yun; Kang, Xuan; Zou, Wei; Wang, Chun-Yan; Zhang, Ping; Tang, Xiao-Qing (Frontiers in Neuroscience, 2020)
Sleep deprivation (SD) induces hippocampal damage. Hydrogen sulfide (H2S) is a neuronal protective factor. Silence information regulating factor 1 (Sirt1) plays an important role in neuroprotection. Therefore, this study was to explore whether H2S meliorates SD-induced hippocampal damage and whether Sirt1 mediates this protective role of H2S. We found that sodium hydrosulfide (NaHS, a donor of H2S) alleviated SD-generated hippocampal oxidative stress, including increases in the activation of SOD and the level of GSH, as well as decrease in the level of MDA. Meanwhile, we found that NaHS reduced SD-exerted hippocampal ER Stress, including downregulations of GRP78, CHOP, and cleaved-caspase-12 expression. Moreover, NaHS reduced the apoptosis in SD-exposed hippocampus, including decreases in the number of apoptotic cells and the activation of caspase-3, down-regulation of Bax expression, and up-regulation of Bcl-2 expression. NaHS up-regulated the expression of Sirt1 in the hippocampus of SD-exposed rats. Furthermore, Sirtinol, the inhibitor of Sirt1, abrogates the protection of NaHS against SD-exerted hippocampal oxidative stress, ER stress, and apoptosis. These results suggested that H2S alleviates SD-induced hippocampal damage by upregulation of hippocampal Sirt1.